2018
DOI: 10.3390/agronomy8090168
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance Water Deficit Improves the Seed Yield and Quality of Soybean

Abstract: Water imbalance condition (WIC) in a maize-soybean relay intercropping system is the main abiotic stress limiting biomass production and seed yield and, consequently, seed-quality. This experiment was started to study the effects of WIC on soybean, in which two soybean genotypes ND12 and C103 were grown in pots with roots split equally between two soil column and six WIC treatments (%) T1 (100), T2, (100:50), T3 (100:20), T4 (50:50), T5 (50:20), and T6 (20:20) field capacity on both sides of soybean roots were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 54 publications
(67 reference statements)
1
10
0
Order By: Relevance
“…In our study, the seed yield of both cultivars decreased significantly as the severity of drought stress increased. This is in line with the earlier research (Desclaux et al 2000, Liu et al 2003, Stolf-Moreira et al 2010, Iqbal et al 2018. However, the results of our study demonstrated a significantly higher seed yield of N12 (under moderate drought stress) and C103 (under severe drought stress) under shade conditions as compared to full light.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the seed yield of both cultivars decreased significantly as the severity of drought stress increased. This is in line with the earlier research (Desclaux et al 2000, Liu et al 2003, Stolf-Moreira et al 2010, Iqbal et al 2018. However, the results of our study demonstrated a significantly higher seed yield of N12 (under moderate drought stress) and C103 (under severe drought stress) under shade conditions as compared to full light.…”
Section: Discussionsupporting
confidence: 93%
“…Drought and shade stress are important environmental factors in determining the biological yield as they affect plant productivity. Various earlier published literature provides an insight into the effect of shade and drought stress separately on soybean yield (Liu et al 2003, Karam et al 2005, Masoumi et al 2011, Yang et al 2014Iqbal et al 2018). Although great research effort has been made towards understanding the effects of shade and drought stress on soybean productivity, little attention has been given to the combined effect of both abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that half-irrigated regime resulted in slightly taller plants compared to the fully irrigated counterpart (except for inoculated plants in 0N treatment); however, drought stress (nonirrigated regime) decreased this trait, regardless of inoculation or fertilization, with the decrease being significant in inoculated plants. Iqbal et al [20] concluded that decreasing available water at the R4 stage from 100 to 50% FC slightly increased plant height in soybean; however, further reduction to 20% FC resulted in shorter plants compared to both 10 and 50% FC. Sepanlo et al [21] also reported that soybean plants had 29.6% shorter plants under drought stress imposed at the flowering stage.…”
Section: Discussionmentioning
confidence: 99%
“…A s they are sessile organisms, plants are often exposed to a variety of abiotic stresses during their life span without any protection. The commonly occurring abiotic stresses that a plant may encounter include the decreased or increased availability of water, alterations in light quality and quantity, extreme temperatures (high or low), and decreased availability of essential nutrients from the soil (Ahmad and Prasad, 2011; Iqbal et al, 2018). In response, plants have evolved mechanisms to maintain a balance among growth, reproduction, and survival under these unfavorable environmental surroundings.…”
mentioning
confidence: 99%